Psolus rufus, a new species of sea cucumber (Holothuroidea: Psolidae) from northern Spain (Bay of Biscay). (18th July 2017) - Fernández-Rodríguez, Irene; Arias, Andrés; Borrell, Yaisel J.; Anadón, Nuria; Massin, Claude; Acuña, José Luis
Abstract : A new species of holothurian of the genus Psolus Oken, 1815 is described. Psolus rufus sp. nov. was found in the central Cantabrian slope (Bay of Biscay) at 1500 m depth. The new species is characterized by having: ovoid body, reddish colour in vivo ; dorsal area enclosed in a complete test composed of imbricating scales; 10 triangular plates of the same size surrounding mouth; 10 oral tentacles; no dorsal papillae; tube feet in two rows in the ventrolateral radii but one single row in the medial third or the body; ossicles are big dorsal plates and small plates in the sole, which are smooth, irregular and perforated. The molecular study of the COI gene supports the morphological results, grouping P. rufus sp. nov. together with other members of the genus. However, the new species is genetically distinct from the two groups (Antarctic and Canadian) of the available sequenced Psolus species. Furthermore, a key to the Psolus species of the north-eastern Atlantic Ocean is provided.